The influence of Perceived Hypermarket Size on Perceived Hypermarket Reputation, Trust and Customer Willingness to Purchase in South Africa - Chinomona, Richard (Journal of Economics and Behavioral Studies, 2015)
While a remarkable increase in research focusing customer purchase intentions in the retailing industry is noticeable, there is a dearth of studies that have investigated the influence of hypermarket size on customer perceived hypermarket reputation, trust in hypermarket and customer willingness to purchase in the African retailing context. This study used a sample 151 consumers in the Vanderbijlpark town in South Africa to examine these relationships. The results indicate that the proposed five hypotheses are positively supported in a significant way. A discussion of the academic and managerial implications of the results is provided and future research directions are suggested.